Supernormal Conduction and Suppression of Spatially Discordant Alternans of Cardiac Action Potentials - Jing, Linyuan; Agarwal, Anuj; Patwardhan, Abhijit (Frontiers in Physiology, 2016)
Spatially discordant alternans (DA) of action potential durations (APD) is thought to be more pro-arrhythmic than concordant alternans. Super normal conduction (SNC) has been reported to suppress formation of DA. An increase in conduction velocity (CV) as activation rate increases, i.e. a negative CV restitution, is widely considered as hallmark of SNC. Our aim in this study is to show that it is not an increase in CV for faster rates that prevents formation of DA, rather, it is the ratio of the CV for the short relative to the long activation that is critical in DA suppression. To illustrate this subtlety, we simulated this phenomenon using two approaches; (1) by using the standard, i.e. S1S2 protocol to quantify restitution and disabling the slow inactivation gate j of the sodium current (INa), and (2) by using the dynamic, i.e. S1S1 protocol for quantification of restitution and increasing INa at different cycle lengths (CL). Even though both approaches produced similar CV restitution curves, DA was suppressed only during the first approach, where the CV of the short of the long-short action potential (AP) pattern was selectively increased. These results show that negative CV restitution, which is considered characteristic of SNC, per se, is not causal in suppressing DA, rather, the critical factor is a change in the ratio of the velocities of the short and the long APs.